Case report: Coexistence of myotonia congenita and Brugada syndrome in one family - Cordenier, Ann; Flamez, Anja; de Ravel, Thomy; Gheldof, Alexander; Pannone, Luigi; De Asmundis, Carlo; Pappaert, Gudrun; Bissay, Véronique (Frontiers in Neurology, 2022)
Myotonia congenita is a rare neuromuscular disorder caused by CLCN1 mutations resulting in delayed muscle relaxation. Extramuscular manifestations are not considered to be present in chloride skeletal channelopathies, although recently some cardiac manifestations have been described. We report a family with autosomal dominant myotonia congenita and Brugada syndrome. Bearing in mind the previously reported cases of cardiac arrhythmias in myotonia congenita patients, we discuss the possible involvement of the CLCN1-gene mutations in primary cardiac arrhythmia.